All kinds of trains - White, Ron (Grosset & Dunlap New York, 1972)
Book about various types of trains throughout history, and the roles they played. Filled with color illustrations.
Original edition published under the title All Sorts of Trains by the Hamlyn Publishing Group. Ltd.
Keywords: trains